Parasympathetic Nerve Function Status in Postmenopausal Women - Naher, Latifa Afrin Dill; Begum, Noorzahan; Begum, Shelina; Ferdousi, Sultana; Ali, Taskina (Journal of Bangladesh Society of Physiologist, 2009)
Background: In postmenopausal women, the risk of cardiovascular diseases gradually increases and alterations in autonomic nerve functions commonly affect cardiac vagal control. Objective: To observe some aspects of parasympathetic nerve function status in apparently healthy post menopausal women. Method: This cross sectional study was carried out in the Department of Physiology Bangabandhu Sheikh Mujib Medical University. In this study, 30 postmenopausal women with age 45 to 60 years were included in group B (study group) and 30 premenopausal women aged 20 to 30 years were taken in group A (control group). They were further divided into group A1(menstrual),A2(follicular), A3(luteal) according to phases of menstrual cycle during which they were studied. Serum estrogen and progesterone levels were measured in postmenopausal women and also during follicular and luteal phases in premenopausal women and were estimated by MEIA technique. To assess parasympathetic nerve function status, three noninvasive cardiovascular reflex tests such as heart rate response to valsalva maneuver, heart rate response to deep breathing and heart rate response to standing were performed in all the subjects. Data were collected by recording ECG in resting conditions. For statistical analysis, unpaired t test and multiple regression analysis was used. Results: In postmenopausal women, serum estrogen and progesterone levels were significantly (p<0.001) lower compared to those of follicular and luteal phases of premenopausal women except progesterone level during follicular phase which was though lower but not statistically significant. Heart rate response to valsalva maneuver were almost similar in all the groups.Heart rate response to deep breathing and heart rate response to standing were significantly lower in group B than those of group A1, A2 and A3 respectively. On regression analysis parasympathetic nerve function in post postmenopausal women showed significant association with estrogen level. Conclusion: From this study it may be concluded that parasympathetic nerve function was lower in postmenopausal women, which may be related to decreased level of estrogen Key Words: Postmenopausal women, Parasympathetic nerve function, Cardiovascular reflex test. DOI: 10.3329/jbsp.v4i1.4064 J Bangladesh Soc Physiol. 2009 June; 4(1): 14-19